Sosialisasi dan Pelatihan Berbagai Jenis Media Sosial sebagai Promosi Peningkatan Kunjungan K1 Kehamilan di Puskesmas Sungai Tabuk 3 Kabupaten Banjar - Handayani, Eka; Anggraini, Septi; Dhewi, Siska; Anwary, Ahmad Zacky; Agustina, Norsita (Jurnal Abdimas Kesehatan (JAK), 2024)
Data from the World Health Organization (WHO, 2017) states that globally around 830 women die every day due to complications during pregnancy and childbirth, with an MMR rate of 216 per 100,000 live births. As many as 99% of maternal deaths are due to problems with pregnancy and childbirth. The recapitulation of the KIA Report for the Sungai Tabuk 3 Public Health Center from January – June 2022 is 45%, while the target for the district itself is around 50%. The implementation method in this community partnership program activity is divided into 2 (two) activities, the first stage is outreach activities and the second stage is through training and assistance in creating social media, in this case WhatsApp business, which is an appropriate social media for promoting health services. Community Service at Sungai Tabuk 3 can be carried out well. The important role of the Village Midwife, Community, Family, neighborhood association, and cadre with community consultation activities as a forum for discussion to understand the problems and needs that exist in the community, Media in the form of Leaflets and Benners which are installed and distributed by residents has been carried out well. The results of community service have shown increase in K1 visits by pregnant women during evaluations and whatsapp business that has been used by midwives can be utilized effectively.